Statin Treatment Induced a Lipogenic Expression Hierarchical Network Centered by SREBF2 in the Liver - Song, Shiyu; Niu, Mengyuan; Liang, Qiao; Wang, Lei; Min, Haiyan; Peng, Yuming; Wang, Hongwei; Gao, Qian (Frontiers in Endocrinology, 2021)
Statin treatment is a major prevention for the treatment of hypercholesterolemia and the management of patients with increased risk of cardiovascular disease (CVD) with an evident protective effect. However, its long-term safety was questioned regarding its potential role in new-onset type 2 diabetes mellitus, and its effect on gene regulation in the liver was not fully understood. Herein, by reanalyzing the transcriptome of the livers of obesity and hypercholesterolemia patients, we showed a multiple module organization that related with various clinical metabolic parameters and identified an expression hierarchical network involving cholesterol and fatty acid syntheses in the liver of statin-treated patients. The key genes of the network were validated by QPCR in the hepatocytes upon statin treatment. The upregulation of the key enzymes involving the synthesis of Acetyl-CoA and the induction of a gentle global acetylation of pan-protein and histone H4 in hepatocytes were observed. The study might provide an overall view on statin effect on transcriptional and post-transcriptional regulation of genes in the liver.